Guinness Book of the 20th Century - Armstrong, Steven; Baker, David [et al.]; Managing Editor: Gould, David (London Guinness World Records, 1997)
A year-by-year chronicle of the twentieth century, highlighting the major news stories, as well as popular events that defined the times.
Include Illustrations and Index.
Keywords: History, Modern